Electrochemical Properties of Peat Particulate Organic Matter on a Global Scale: Relation to Peat Chemistry and Degree of Decomposition. Issue 2 (16th February 2022) - Teickner, Henning; Gao, Chuanyu; Knorr, Klaus‐Holger
Abstract: Methane production in peatlands is controlled by the availability of electron acceptors for microbial respiration, including peat dissolved organic matter (DOM) and particulate organic matter (POM). Despite the much larger mass of POM in peat, knowledge on the ranges of its electron transfer capacities—electron accepting capacity (EAC), and electron donating capacity (EDC)—is scarce in comparison to DOM and humic and fulvic acids. Moreover, it is unclear how peat POM chemistry and decomposition relate to its EAC and EDC. To address these knowledge gaps, we compiled peat samples with varying carbon contents from mid to high latitude peatlands and analyzed their EACPOM and EDCPOM, element ratios, decomposition indicators, and relative amounts of molecular structures as derived from mid infrared spectra. Peat EACPOM and EDCPOM are smaller (per gram carbon) than EAC and EDC of DOM and terrestrial and aquatic humic and fulvic acids and are highly variable within and between sites. Both are small in highly decomposed peat, unless it has larger amounts of quinones and phenols. Element ratio‐based models failed to predict EACPOM and EDCPOM, while mid infrared spectra‐based models can predict peat EACPOM to a large extent, but not EDCPOM . We suggest a conceptual model that describes how vegetation chemistry and decomposition control polymeric phenol and quinone contents as drivers of peat EDCPOM and EACPOM . The conceptual model implies that we need mechanistic models or spatially resolved measurements to understand the variability in peat EDCPOM and EACPOM and thus its role in controlling methane formation. Plain Language Summary: Peatlands accumulated large amounts of carbon via photosynthesis and slow decomposition of senesced plant material. Microorganisms within the peat form methane. For this reason, peatlands are important global sources of the greenhouse gas methane and therefore can contribute to climate change. In order to produce methane, the microorganisms have to transfer electrons between compounds in respiration processes. Only recently, it has been found that the peat itself can reversibly transfer electrons and that its capacities to reversibly accept electron accepting capacity (EAC) and reversibly donate electron donating capacity (EDC) electrons are large. We investigated which conditions favor large or small EAC and EDC of peat so that we can better explain methane formation. We argue that vegetation and decomposition control the amount of phenols and quinones—molecules in the peat that presumably are responsible for most of the peat's EAC and EDC. The EAC and EDC probably are largest for peat formed from vegetation rich in quinones and phenols, such as shrubs, and smaller for other vegetation types, for example, certain mosses. Intense decomposition may reduce both the EAC and EDC. Key Points: Peat particulate organic matter electron accepting and donating capacities per grams of carbon are smaller than for humic and fulvic acids Both capacities are small in highly decomposed peat, unless it has larger amounts of quinones and phenols We explain these patterns with parent vegetation chemistry and conditions during decomposition